Affective registers in qualitative team research: interpreting the self in encounters with the state. (3rd May 2016) - Jakimow, Tanya; ., Yumasdaleni
Abstract : Purpose: – The purpose of this paper is to present an approach to enhance understandings of personhood and self-becoming through an affective reading of field notes and interview transcripts in cross-cultural research teams. Design/methodology/approach: – A research team in Medan, Indonesia, captured the affective and emotive aspects of a research scene in field notes that were subsequently shared. Through prompting and elaboration, researchers were able to reveal the pathways from affect to emotion and thought, and the influence of past affective pedagogies in interpretations of the scene. Findings: – Team research can enhance the interpretations of the "self" by drawing upon the diversity of affective registers of researchers. Paying attention to, and discussing in detail the ways researchers are affected in the field provided analytical insights as to the processes of self-becoming made possible within a particular encounter. These insights also added analytical value in team interpretations of interview transcripts. Research limitations/implications: – Hierarchies within teams, communicating across different languages and the difficulty of sharing personal and embodied responses are barriers to using affective registers in team research. Originality/value: – The authors' experiences highlight the value of a purposeful strategy to share and interrogate affective responses, and demonstrate that affective registers are an overlooked resource in qualitative research teams.